IS THE WHEELCHAIR FENCING CLASSIFICATION FAIR ENOUGH? A KINEMATIC ANALYSIS AMONG WORLD-CLASS WHEELCHAIR FENCERS - Fung, Ying-Ki; Chan, King-Chung Derwin; Caudwell, M. Kim; Chow, Bik-Chu (European Journal of Adapted Physical Activity, 2013)
The purpose of this study was to employ a kinematic analysis to determine the extent to which the Wheelchair Fencing Classification (WFC) can reliably predict and classify wheelchair fencers' trunk functional ability, during WFC functional classification assessment condition (without supporting bar) and competition condition (with supporting bar). Participants were 14 world-class wheelchair fencers from Hong Kong, with 9 WFC category A and 5 WFC category B fencers. Participants performed wheelchair fencing actions (i.e., lunge and fast-return) in two conditions (i.e., standard WFC testing condition and wheelchair fencing in competition condition). The maximum trunk velocity and maximum trunk angle (i.e., range of movement) were motion-captured and analyzed by kinematic analysis. The results showed that WFC classification significantly correlated with the trunk functional ability in the WFC testing condition, but not in the competition condition. The functional ability indices were significantly higher in the competition condition than that in the WFC testing condition for fencers of both category A and B. The trunk functional ability of category A fencers was significantly higher than that of category B fencers in a WFC testing condition, but such patterns were not observed in the competition condition. We concluded that the WFC test might not be fair and reliable enough to classify fencers according to the impact of their impairments on wheelchair fencing competitive performance.